Analysis of Clinical Pathway Implementation of Urinary Tract Stones at Royal Prima General Hospital Medan - Subkhan Subkhan; Tri Suci; Sri Lestari Ramadhan (International Journal of Health and Pharmaceutical (IJHP), 2023)
In realizing individual health rights, health services are required to be able to place resources and organization efficiently with the advancement of medical world. Clinical pathway (CP) is a disease management tool used to reduce unnecessary variations in services to improve clinical outcomes and to control the use of resources (financial). Acute appendicitis is one of the most common causes of acute abdominal pain, with cases from 20-30% and increasing 32-72% at age of <60 years. Therefore, it is necessary to conduct a study on the implementation of CP in the RSU. Royal Prima Medan. This study was conducted by using mix method with a case study design. Qualitative data were taken by interview and observation with case manager, medical committee, and nurses (n = 5) and quantitative data were taken with simple descriptive from acute appendicitis CP documentation in medical records and ICPAT (January - September 2020, n = 117). The level of completeness for CP was 100% and form filling was 85%. ICPAT dimension 1 contents and quality are good, dimension 2 contents still lack, and quality is moderate, dimension 3 contents is good and quality is moderate, dimension 4 content in moderate criteria and quality is good, dimension 5 contents still lack and quality is moderate and dimension 6, contents is good and quality is in moderate category. Where the obstacles are due to lack of understanding and time constraints. The development of urinary tract stones CP is not quite optimal; it is necessary to conduct periodic socialization and training to support understanding in filling out CP.